The role of high-yield bonds in strategic asset allocation over the Great Recession - Menounos, Georgios; Alexiou, Constantinos; Vogiazas, Sofoklis (LLC “Consulting Publishing Company “Business Perspectives”, 2017)
By utilizing a modified version of the Black-Litterman model, the authors explore the asset allocation to high-yield bonds based on an investor’s risk profile. In so doing, the researchers use US data on high-yield bonds and over the period 2007–2013. The key finding relates to the strategic asset allocation to high-yield bonds in a simulated global market portfolio depending on an investor’s risk tolerance. In particular, the share of high-yield bonds does not exceed 4.15% of total assets in a global market portfolio over the period 2007–2013, whilst the allocation remains relatively stable and small on a risk-adjusted basis, irrespective of an investor’s risk profile or the phase of the business cycle. In simple terms, the results suggest that high-yield bonds do not seem to merit a favorable treatment in the asset allocation process relative to other financial instruments in a global market portfolio.
Keywords: lack-Litterman model; high-yield bonds; asset allocation; global financial crisis